“Fear of the Unknown”: Coparenting With an Incarcerated Individual - Tadros, Eman (International journal of offender therapy and comparative criminology, 2024)
Over 2.2 million individuals are currently incarcerated in prisons and jails across the United States. Having a family member incarcerated impacts the entire family system. Recent research has shown the relational consequences of incarceration, such as adjusting to and negotiating new rules and roles within the coparenting relationship. The coparenting relationship is multifaceted and necessitates empirical evidence that significantly honors the voices that are at the center of experience but typically silenced by the stigma and prejudice nature of incarceration and its coinciding consequences. Coparenting partners of incarcerated individuals were interviewed to understand the lived experience of incarcerated coparenting using a phenomenological approach. Four themes (positive relationship, stigma, seeking and providing support, and impact of incarceration) emerged from eleven interviews. Implications are provided on how to best advocate for this population through research, clinical work, and policy.